Efficacy and safety of 15(R/S)‐methyl‐lipoxin A4 in topical treatment of infantile eczema. (21st December 2012) - Wu, S.‐H.; Chen, X.‐Q.; Liu, B.; Wu, H.‐J.; Dong, L.
Summary: Background Lipoxins are potential anti‐inflammatory mediators and serve as an endogenous 'braking signal' in the inflammatory process. Accumulating evidence has indicated the efficacy of lipoxin A4 (LXA4 ) and its analogs in the treatment of many animal models of inflammatory diseases. Objectives This study investigates the efficacy and safety of 15(R/S)‐methyl‐lipoxin A4 in the topical treatment of infantile eczema. Patients and methods In this two‐centre, double‐blind, placebo‐controlled, randomized, parallel‐groups comparative study, 60 patients were randomly assigned to receive either the 15(R/S)‐methyl‐lipoxin A4 cream, mometasone furoate (Eloson, Schering‐Plough, Shanghai, China) or placebo for 10 days. The efficacy was determined using the Severity Scale Score (SSS), Eczema Area and Severity Index (EASI) and the Infants' Dermatitis Quality of Life Index (IDQOL). Safety was monitored by physical examination, laboratory investigation and documentation of clinical adverse events. Results The treatment of eczema with 15(R/S)‐methyl‐LXA4 cream significantly relieved the severity, induced a recovery, and improved the quality of life of the patients, as demonstrated by significantly reduced SSS, EASI and IDQOL, respectively, in a way similar to the efficacy of Eloson. All safety parameters remained within normal limits. No clinical adverse event was found in the three patient groups. Conclusions 15(R/S)‐methyl‐LXA4 was well tolerated, and significantly reduced the severity of eczema. The results of this small exploratory study suggest that 15(R/S)‐methyl‐LXA4 warrants further investigation in the treatment of eczema.